The Role of Digitalization in Moderating the Effect of Corporate Governance On a Bank’s Financial Performance - Juliani Setiawan; Triasersiarta Nur (Eduvest - Journal of Universal Studies, 2025)
This research aims to analyze the effect of digitalization on the relationship between corporate governance and bank performance by examining publicly listedbanks in Indonesia. This research utilized a sample of 327 firm-year observations from 38 banking entities publicly listed on the IDX for the period 2013-2023. Regression analyses using the random-effect, robust clustered standard error are performed on the data set to test the hypothesis. Results of empirical analyses showed that size of board of commissioners and board of directors are both negatively associated with a bank’s performance (ROE). When proxy for digitalization are introduced, the results show that the interaction has positive effect on ROE. This implies that the introduction of digitalization in a bank has a buffering effect on the negative impact of large board sizes. The result remains robust in alternative testing. This research utilized the interaction between corporate governance variables and proxies for digitalization as moderating variable, allowing for the examination of how digitalization moderates the relationship between governance structures and bank performance. The results observed from this research imply that the digitalization in banks has the potential to buffer the negative impacts of board size on a bank’s performance.